2021
DOI: 10.1093/infdis/jiab616
|View full text |Cite
|
Sign up to set email alerts
|

Similar Risk of Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Similar Nucleocapsid Antibody Levels in People With Well-Controlled Human Immunodeficiency Virus (HIV) and a Comparable Cohort of People Without HIV

Abstract: Background Within the ongoing AGEhIV Cohort Study in Amsterdam, we prospectively compared the incidence of and risk factors for SARS-CoV-2 infection between HIV-positive and -negative participants. Moreover, we compared SARS-CoV-2 nucleocapsid antibody levels between participants with incident infection from both groups. Methods Starting in September 2020, consenting HIV-positive and HIV-negative participants were assessed 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
8
2
Order By: Relevance
“…Since the beginning of the pandemic, there has been concern that PWH are less likely to develop and maintain protective immunity. While some studies suggested lower humoral responses in PWH [6], we and others [36][37][38] have not observed this. to a more exhausted phenotype.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Since the beginning of the pandemic, there has been concern that PWH are less likely to develop and maintain protective immunity. While some studies suggested lower humoral responses in PWH [6], we and others [36][37][38] have not observed this. to a more exhausted phenotype.…”
Section: Discussioncontrasting
confidence: 89%
“…Since the beginning of the pandemic, there has been concern that PWH might be less likely to develop and maintain protective immunity. While some studies suggested lower humoral responses in PWH [14], this did not appear to translate into a higher risk of re-infection in the pre-vaccine era, and several other studies did not find substantial differences following natural infection in PWH on suppressive ART [68][69][70]. Although some early data suggest that vaccine-induced immunity could be less robust among PWH, it appears to be driven by the population of PWH with low CD4+ cell counts [71].…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing concern that PWH are less likely to develop and maintain protective immunity. Although some studies suggested lower humoral responses in PWH [6], we and others [36][37][38] have not observed this.…”
Section: Discussioncontrasting
confidence: 88%
“…PLWH in South Africa with well-controlled HIV-1 also demonstrated 6 similar antibody kinetics, durability, and neutralization potency as PWOH (12). Similar antibody levels against the spike protein and nucleocapsid were reported in small PLWH cohorts in Japan (13) and the Netherlands (14), respectively. In contrast, other studies reported a marked decline of antibody responses within 2 months of SARS-CoV-2 infection among PLWH (15) with diminished seroconversion and shorter duration of antibody responses than PWOH (16).…”
Section: Introductionsupporting
confidence: 76%